2019
DOI: 10.1038/s41598-019-46341-2
|View full text |Cite
|
Sign up to set email alerts
|

Cassava cell wall characterization and degradation by a multicomponent NSP-targeting enzyme (NSPase)

Abstract: Cassava ( Manihot esculenta Crantz) is considered the third most important source of calories in tropical regions. Up to one third of cassava harvested worldwide is used in livestock production. The focus of this study was to characterize cassava cell wall structure to provide knowledge for a better application of cassava as an energy source in monogastric animal feed. A total of five cassava samples from different feed mills in South East Asia were investigated. On a dry matter basis, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 40 publications
(39 reference statements)
1
5
0
Order By: Relevance
“…Treatments NFC2 and NFC3 contained cassava meal at 20-30% DM. Cassava meal is rich in carbohydrates, especially pectin, producing a high proportion of acetate [41]. This finding aligns with previous studies, which reported a high molar proportion of acetate in pectin-rich rations [42,43].…”
Section: Fermentation Characteristicssupporting
confidence: 92%
“…Treatments NFC2 and NFC3 contained cassava meal at 20-30% DM. Cassava meal is rich in carbohydrates, especially pectin, producing a high proportion of acetate [41]. This finding aligns with previous studies, which reported a high molar proportion of acetate in pectin-rich rations [42,43].…”
Section: Fermentation Characteristicssupporting
confidence: 92%
“…Meanwhile, the intestinal microbiota plays a critical role in host nutrition, health, performance and quality of meat products given that the microbiota in the GIT can degrade undigested substrates and create SCFA and oligosaccharides from cell wall NSP, which act as an additional energy source and exhibit potential prebiotic effects, respectively . The chemical composition and structure of the substrates largely determine the (changes in) microbial composition of the bacterial community in the GIT given that microbes exhibit differences in substrate preferences (degradation capacity) and growth requirements. , As a result, microbial composition and metabolic function are very much dependent on biochemical conditions of digesta.…”
Section: Introductionmentioning
confidence: 99%
“…Immunolabeling of pectin by JIM7 and 2F4 antibodies was performed as described by Christiaens et al (2011) and LM9 antibody as described by Staack, Della Pia, Jørgensen, Pettersson and Rangel Pedersen (2019). After the incubation with antibodies, the sections were excited at 460-495 nm wavelengths and examined with the Olympus BX-41 microscope (Olympus, Optical Co. Ltd., Tokyo, Japan) equipped with epifluorescence illumination (DM505, excitation wavelength 460-495 nm).…”
Section: Immunolabeling Of Pectic Epitopesmentioning
confidence: 99%